2009
DOI: 10.1592/phco.29.8.993
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Seizure Associated with Paclitaxel‐Cremophor EL in a Patient with Early‐Stage Breast Cancer

Abstract: Paclitaxel, a microtubule stabilizer, is an effective agent for treating cancer of the breast, ovary, head and neck, and lung. Because paclitaxel is insoluble in water, it is formulated with the micelle-forming Cremophor EL. Neurologic toxicity is well described with both the drug and this carrier, with most toxicities manifesting as peripheral neuropathy, motor neuropathy, autonomic neuropathy, and myopathy. Toxic effects on the central nervous system, such as seizures or encephalopathy, have been rarely repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Many of these drugs are delivered as cocktails [5,10]. While newer, water-soluble compounds are being developed for their potential anti-breast cancer efficacy [11][12][13][14][15], delivery and specificity remain major obstacles [16]. In all cases, side effects can be devastating and during treatment, the patient's quality of life is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these drugs are delivered as cocktails [5,10]. While newer, water-soluble compounds are being developed for their potential anti-breast cancer efficacy [11][12][13][14][15], delivery and specificity remain major obstacles [16]. In all cases, side effects can be devastating and during treatment, the patient's quality of life is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Tracey et al [69] reported on one patient who was treated by paclitaxel formulated using Cremophor EL and who then developed delayed onset of seizures 4 days after drug infusion. There was no history of seizures, and no metabolic lesion was present.…”
Section: Toxicity Of the Carriermentioning
confidence: 99%
“…There was no history of seizures, and no metabolic lesion was present. These researchers believed that the seizures were caused by paclitaxel or its carrier [69]. Because paclitaxel is insoluble in water, it is formulated with the micelle-forming Cremophor EL.…”
Section: Toxicity Of the Carriermentioning
confidence: 99%
See 1 more Smart Citation
“…CrEL is considered to be mainly responsible for peripheral neuropathy, which elicits the sensory symptoms (numbness, tingling, and burning pain) associated with the administration of formulation agents, [1][2][3][4] as well as for central neuropathy causing seizures. 5,6) One mechanism exerting the neurotoxicity of CrEL is thought to be based on disturbances in the microtubules in neurons. 7) Rat dorsal root ganglia (DRG) neurons and mouse neuroblastoma cells exposed in vitro to CrEL showed axonal degeneration and demyelination.…”
mentioning
confidence: 99%